Identification Of Community Prosperity Levels In Waiya Village, Depapre District, Jayapura Regency - La Alimuddin, Yotam Senis, Fitrine Ch. Abidjulu, Rima Nusantriani Banurea, Lazarus Ramandei (International Journal of Advanced Science and Technology, 2020)
Impoverished condition is the inability of an individual/or group to meet the basic needs of their life which includes clothing, food, and shelter. Waiya Village is one of the villages that has problems with community prosperity. One problem is that efforts have not yet been directed at community prosperity. It is caused by lack of information and data regarding community prosperity. The current research aims to determine the grouping of community prosperity levels and to know BUMKam’s strategy in overcoming prosperity problems in Waiya Village. This research applies several research methods which include field study, research implementation, data collection, data processing, data analysis and presentation of research results. To obtain data and information, the researchers employ observation, interview, and questionnaire techniques. The data will be processed using qualitative descriptive analysis, root of the problem, and SWOT analysis. After going through the identification process, Waiya Village is grouped into 4 levels of community prosperity. The community groupings include: (1) Pre-prosperous (very poor) 3%; (2) Prosperous I (poor) 15%; (3) Prosperous II (vulnerable to poverty) 23%; and (4) Prosperous III (prosperous) 53%. To minimize prosperity issues in Waiya Village, BUMKam uses an aggressive strategy by opening programs/activities that can increase the income and quality of human resources by considering the potential and advantages of Waiya Village. The next strategy is to promote programs/activities that have been developed by BUMKam to provide opportunities for village communities.